Health Education and Utilization of Turmeric Rhizomes for the Prevention of Diabetes Mellitus - Widyani, Retno; Agustin, Gysella Aedeliya; Hermawan, Andri (Ann Publisher, 2025)
Background. Diabetes Mellitus is a chronic disease whose number of sufferers is increasing every year and causes various serious health problems. Preventing this disease can be achieved by improving health literacy and using medicinal plants from the family (TOGA). One plant with potential is turmeric (Curcuma longa L.), which contains curcumin, a natural antidiabetic agent. Purpose. Providing understanding to the public about the prevention of Diabetes Mellitus, as well as training skills in processing turmeric rhizomes as a complementary therapy. Method. The methods used include initial surveys, health education, the practice of making herbal turmeric drinks, and evaluation using pre- and post-tests. Result. The results of the activity showed an increase in public knowledge of risk factors for Diabetes Mellitus, understanding the benefits of turmeric, and the ability to make simple herbal remedies. Conclusion. With this activity, the community is expected to adopt a healthy lifestyle grounded in local wisdom through the sustainable use of TOGA.